Anti-NMDA Encephalitis: A Rare Encephalitis in a Child- A Case Report - Khetan, Saurav; Agrawal, Nikhil; Rajoli, Prakash (Medical Journal of Shree Birendra Hospital, 2020)
Anti-NMDA encephalitis is second commonest cause of autoimmune encephalitis among children; however, it is hardly diagnosed and often not considered as one of the differentials when a child presents with encephalitis-related symptoms. In children, it presents mostly with seizures or psychiatric symptoms without prodrome. Here we present a six years old girl who presented with seizures and inappropriate behaviour. We investigated her in the line of viral encephalitis such as Japanese Encephalitis, which is very common in our region. However, results were not suggestive of Japanese Encephalitis and further investigations subsequently lead to diagnosis of anti- NMDA encephalitis. This is probably one of the first case report of this disease in our country. We want to highlight the significance of high index of suspicion for looking out for an organic cause in any child who presents with psychiatric symptoms, along with seizures.